Problem identification and conceptualization in educational research concepts, principles and methods - Cortes, Josefina R. (Education quarterly.)
This paper has three objectives: (1) to underscore the importance of conducting scientific research in education, (2) to discuss the elements and requirements of educational research as a scientific inquiry undertaking, and (3) to describe and demonstrate the basic principles and techniques involved in a scientific inquiry, specifically, problem identification and problem conceptualization.